(untitled) (Journal of Hama University, 2026)
The study aimed to investigate the effect of a group of medicinal plant extracts on some Blood Parameter and biochemical parameters in the blood of Awassi ewes. The study was conducted on 24 ewes, aged between 2 and 3 years and weighing an average of 46 and 54 kg. The experimental animals were randomly assigned to four groups, with six ewes per group. The first group was considered the control group. The remaining groups were given: (2) Glycyrrhizin glubara extract (400 mg/kg), (3) salvia officinalis extract (500 mg/kg), and (4) Rosmarinus officinalis extract (400 mg/kg). The study lasted 30 days. At the end of the experiment, blood samples were obtained from the experimental animals and analyzed in the laboratory to determine the total red blood cell (RBC) and white blood cell (WBC) counts, hemoglobin (Hg) levels, and hematocrit (HCT) levels, in addition to cholesterol and triglyceride levels. The results showed a significant superiority at the level of P≤0.05 in the average red blood cell count, hemoglobin level, and hematocrit percentage of the study animals in the second and third groups compared to the control group, in addition to a significant superiority at the level of P≤0.05 in the average white blood cell count of the study animals in the second group compared to the control group. The study also showed a significant decrease at the level of P≤0.05 in the level of cholesterol and triglycerides in the study animals in the second and fourth groups compared to the control group.